Toward a Theory of the Development of Unionism in the U.S. - Massie, Joseph (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1959)
SummaryThe purpose of this article is to extract from the writings in the labor literature some of the basic concepts which have developed within unionism in the United States. Periodically, such a summary is desirable because of the diverse set of disciplines which are involved. The deficiencies in securing better understanding in this area of thought are not the result of a lack of profound and incisive study by specialists, but are the result of the lack of awareness by practitioners of the underlying threads of thought which have been spun already. This will be an attempt to weave some of these threads into pieces of cloth; it will be an integration of some concepts into a hypothesis of unionism in the United States.